Effect of Substrate Temperature on Optical Properties of Cu2ZnSnS4 Thin Films Preparing by Chemical Spray Pyrolysis Technique - Alaa Ali Diwan (Journal of Global Pharma Technology, 2016)
The optical properties of thin films of Cu2ZnSnS4 have been studied by deposited on glass substrate by chemical  splash spray pyrolysis method (CSP) ,with constant concentration and different substrate temperatures of (350, 400 and 450) °C. CZTS films were prepared by chemical spray pyrolysis by dissolving of copper (II) chloride (CuCl2), zinc (II) Zn (CH3COO).2H2O, tin (IV) chloride (SnCl4), and Thiourea (CS (NH2)2 ,were utilized as sources of Copper particles, Zinc particles, Tin particles and Sulfur particles individually. The UV-Vis study showed high optical absorption coefficient and wide direct band gap for solar region. Further the optical constants such as refractive index, extinction coefficient and dielectric constant have been calculated for all samples. The optical energy gap for permitted direct electronic progress was determined utilizing Tauc's equation.  It is discovered that the band gap diminishes as the substrate temperature increments and the optical permitted energy gap for the direct electronic transitions was in the range of (2-2.2) eV.  The optical absorption coefficient is found to be larger than (10 4 cm-1), which respectively these films have a direct transition.Keywords: CZTS thin Films, Spray pyrolysis Technique, Optical properties, Еnеrgy gap.